From resource allocation to strategy - Bower, Joseph L.; Gilbert, Clark G. (Oxford : Oxford University Press, 2005)
The papers in this volume, and the decades of work on which they build, document the complexity and subtlety of the processes that generate firm' resource allocation decisions and, thereby, their strategies. This work raises issues of the extent to which the predictions of standard theories of the capital allocation process are accurate, given that the theoretical models typically do not reflec the documented institutional realities.
Linking resource allocation to strategy / Joseph L. Bower, Yves L. Doz, Clark G. Gilbert -- Modleing the resource allocation process / Joseph L. Bower -- The role of strategy making in organizational evolution / Robert A. Burgelman -- Anomaly-seeking research : thirty years of theory development in resource allocation theory / Clark G. Gilbert, Clayton M. Christensen -- When the bottom-up resource allocation process fails / Donald N. Sull -- Customer power, strategic investment, and the failure of leading firms / Clayton M. Christensen, Joseph L. Bower -- No exit : the failure of bottom-up strategic processes and the role of top-down disinvestment / Donald N. Sull -- The process of international expansion : comparing established firms and entrepreneurial start-ups / Walter Kuemmerle -- Restoring the bottom-up process of resource allocation / Clark G. Gilbert -- Strategy making as an iterated process of resource allocation / Tomo Noda, Joseph L. Bower -- Beyond resource allocation : how definition and impetus interact to shape strategic outcomes / Clark G. Gilbert -- Corporate intervention in resource allocation / Thomas R. Eisenmann -- The entrepreneurial m-form : a case study of strategic integration in a global media company / Thomas R. Eisenmann, Joseph L. Bower -- Strategic flexibility : corporate-level real options as a response to uncertainty in the pursuit of strategic integration / Michael E. Raynor -- Resource allocation processes in multidimensional organizations : MNCs and alliances / Yves L. Doz -- Resource allocation, strategy, and organization : an economist's thoughts / John Roberts -- Comments on the resource allocation process / Daniel A. Levinthal -- Research complementarities : a resource-based view of the resource allocation process model (and vice versa) / Margaret A. Peteraf -- CEO as change agent? / Joel M. Podolny -- A revised model of the resource allocation process / Joseph L. Bower, Clark G. Gilbert.
Includes bibliographical references and index.
gau 06/06/14
Loans
Keywords: Strategic planning; Resource allocation -- Decision making; Capital budget; Strategisch management; Strategische planning